PEMBUATAN YOGHURT SINBIOTIK KACANG MERAH (Phaseolus vulgaris L.) DENGAN PENGGUNAAN BAKTERI ASAM LAKTAT DENGAN PENAMBAHAN PREBIOTIK - Agatha Sonya Sekarningrum; Seveline Umar (Universitas Trilogi, 2020)
Manufacture of probiotic product that has been done a lot is manufacture of yoghurt. In the process, addition of red beans and prebiotic is done to add value to the product. Addition of Lactic Acid Bacteria and inulin in the form of banana flour with different amounts is done to find the right synbiotic yogurt formulation. This research was conducted to test the quality of product physically, chemically, microbiology and organoleptics. This research was conducted using a Completely Randomized Design with the first factor being the BAL levels added and the second factor being the levels of inulin added. Based on the tests, the results obtained that the formulation using L. plantarum as much as 1% and 2% commercial inulin is the right formulation with results that are in accordance with SNI 2891: 1992 standards. The total value of LAB resulting from the formulation is 3.24 x 106 cfu/ml with a total non-fat solid of 11.16%.Keywords: banana flour,inulin, Lactobacillus casei, Lactobacillus plantarum.